Hubungan Kecerdasan Spasial dan Kemampuan Penalaran Matematis Peserta Didik Dalam Menyelesaikan Masalah Geometri - Zuhria Sya’bani, Gita; Hikmah, Nurul; Novitasari, Dwi; Sarjana, Ketut (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
This study aims to find out whether there is a significant relationship between spatial intelligence and the mathematical reasoning ability of class IX MTs Negeri 2 Mataram students in solving geometry problems. This type of research is correlational research. The sample in this study was students of class IX A MTs Negeri 2 Mataram who were taken with purposive sampling techniques. Data collection is carried out using test instruments in the form of description questions about spatial intelligence, reasoning ability, and solving geometric problems. The data were analyzed using descriptive statistics and correlation tests with a quantitative approach. The results of the data analysis showed: 1) there was a significant relationship between spatial intelligence and solving geometry problems of class IX MTs Negeri 2 Mataram students of 0.366 with a weak relationship category; 2) there is a significant relationship between mathematical reasoning ability to solve geometric problems of class IX MTs Negeri 2 Mataram students of 0.386 with a weak relationship category; 3) there is a significant relationship between spatial intelligence and mathematical reasoning ability of class IX MTs Negeri 2 Mataram students in solving geometric problems of 0.532 with sufficient relationship categories.